(untitled) (Филолошке студије, 2019)
This article is presented the attitude of U. Eco and J. Borges towards the main problems of philosophy of language: representation and naming. The following issues have been analysed in the text: the relations between language, reality, cultural universe (medieval philosophy studies) and representation. From our point of view, the problem of naming (the name of rose) has to be studied in multidisciplinary context of semiotics, linguistics, logic, philosophy and even artistic (fiction) discourse. The processes of representation and giving the names to objects of reality are based on the realism and nominalism as the main epistemological positions of medieval philosophy. From the realist point of view, reality consists of ideas of things, or every thing is the realization of its idea that existed before things (оба дивных кота – и в зеркале, и во плоти – подобья одного вневременного прообраза). So if we want to represent reality, we use general names as main signs. The dividing line between general and individual names concerns not only of objects they stand for (refer to), but also the manifestation form of signs. Our language has the same sign for naming individual thing (this rose) and class of things (rose as a type). For distinction these signs we have to add attributes (predicate signs) to things (their names) which are being described. So the name without predicate is classifed as general name. In discussion of universalia U. Eco and J. Borges joins to realists, that is why thee refer to essence, to idea of rose and doesn’t describe it’s attributes. Their semiotic conception we define as naming of essence.